Attitudes to mathematics in primary school children - Dowker, A; Bennett, K; Smith, L (Hindawi, 2012)
44 Grade 3 children and 45 Grade 5 children from English primary schools were given the British abilities scales basic number skills subtest, and a Mathematics Attitude and Anxiety Questionnaire, using pictorial rating scales to record their Self-rating for maths, Liking for maths, Anxiety about maths, and Unhappiness about poor performance in mathematics. There were few year group differences in attitudes. Boys rated themselves higher than girls, but did not differ significantly in actual performance. Overall, Anxiety was not related to actual performance, but Self-rating was. This relationship between Self-rating and actual performance seemed to develop between Grade 3 and Grade 5. Implications of the findings are discussed.